2014
DOI: 10.1002/cbin.10237
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of human umbilical vein endothelial cell gene expression in different biomechanical environments

Abstract: Biomechanical environments affect the function of cells. In this study we analysed the effects of five mechanical stimuli on the gene expression of human umbilical vein endothelial cells (HUVECs) in mRNA level using real-time PCR. The following loading regimes were applied on HUVECs for 48 h: intermittent (0-5 dyn/cm(2) , 1 Hz) and uniform (5 dyn/cm(2) ) shear stresses concomitant by 10% intermittent equiaxial stretch (1 Hz), uniform shear stress alone (5 dyn/cm(2) ), and intermittent uniaxial and equiaxial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…16,41,43,44 The SMC orientation response is consistent with the response that has been found for many different cell types such as ECs, osteoblasts, fibroblasts, and melanocytes. 23,40,41,45,46 The results for the cell orientation support the common hypothesis that cell alignment is an avoidance reaction of the cells exposed to tension. It is believed that the sensing of cells is mediated by cell-matrix adhesions that mechanically link the extracellular matrix with the cytoskeleton.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…16,41,43,44 The SMC orientation response is consistent with the response that has been found for many different cell types such as ECs, osteoblasts, fibroblasts, and melanocytes. 23,40,41,45,46 The results for the cell orientation support the common hypothesis that cell alignment is an avoidance reaction of the cells exposed to tension. It is believed that the sensing of cells is mediated by cell-matrix adhesions that mechanically link the extracellular matrix with the cytoskeleton.…”
Section: Introductionsupporting
confidence: 76%
“…3 Thus, the behavior of vascular cells such as ECs and SMCs cultured on stretchable substrates which were periodically stretched and relaxed is of interest and was analyzed by various investigators. 23,25,33,36,38,42,43,52,53 These studies have shown that vascular cells tend to align perpendicular to the direction of strain independently of their animal or tissue origin. This suggests that, irrespective of cellular species and tissue and irrespective of the usage of primary cells or non-vascular cell lines, mechanical stressinduced cellular alignment is a common behavior of adhesive cells in vitro, which may operate to induce cellular orientation in tissues in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, trans-differentiation of ECs to SMCs has been observed when stretch is applied to cells. Specifically, SMC marker genes (SM22-α, α-SMA, caldesmon-1, SM MHC and calponin) were increased by stretch, whereas a subsequent reduction in endothelial markers was observed [ 83 , 84 ]. The presence of SMC markers on EC suggests EC plasticity towards SMC phenotype occurs during mechanical stretch, and this may contribute to the development of atherosclerosis.…”
Section: Pathological Implications Of Mechanical Stretchmentioning
confidence: 99%
“…Vascular tissue regeneration using nanofibers with a dynamic milieu has also been attempted, as nanofibers can establish a mechanically active native environment, ECM remodeling with microcapillary formation [102]. The strategy employing a dynamic system is used to build up the mechanical strength and control the cellular functions in synthetic vascular grafts [103]. ECs cultured on collagen/poly(lactic‐ co ‐glycolic acid) (PLGA) fibers were found to be oriented as a native vessel along with the upregulation of vWF and nitric oxide under mechano‐active conditions with respect to static conditions.…”
Section: Influence Of Nanofibers On Endothelial Gene Expressionmentioning
confidence: 99%